Survival of colorectal cancer patients treated at the Oncology Unit, Teaching Hospital Karapitiya, Galle from 2011 to 2013 - De Silva, H. R. T.; Perera, S. C. R.; Daluwakgoda, V. (My University, 2020)
Colorectal cancer (CRC) is the commonest malignancy in the gastrointestinal tract. It is the third most common cancer of both sexes in the world. It comprised 10.2% of all cancers in 2018. Incidence rates of CRC are increasing in developing countries and survival rates of CRC vary widely. Thus, the aim of the study was to determine two and five year overall survival and its predictors of CRC patients treated at the Oncology Unit, Teaching Hospital, Karapitiya (THK) from 2011 to 2013. A retrospective study was conducted among 151 CRC patients treated at the Oncology Unit, THK from 2011 to 2013. The patients were followed up till 30th September 2020. The patients with secondary CRC were excluded. Clinic records of the Oncology unit were referred to collect data. Patients who had stopped clinic visits were contacted via telephone and letters to identify their current status. Kaplan Meier and Cox’s proportional hazards model were used to model survival. The mean survival times of two year and five-year survival were 21.29 months (SD=5.18) and 44.56 months (SD=20.60) respectively. The median survival times of two year and five-year survival were 24 months and 60 months respectively. The commonest age group was 55 to 64 years (32.5%). The commonest stage of lesions was “Duke’s C” (26.5%). Duke’s stage, nodal status and presence of metastases were statistically significant (P<0.001) independent predictors of survival. Duke’s stage was statistically significant (P<0.001) predictors of survival after controlling for other variables. More than two third of patients (71.5%) survived two years and more than half of the patients (60.3%) survived five years. Duke’s stage was a significant predictor of survival in CRC patients treated at the Oncology Unit, THK.

Colorectal cancer (CRC) is the commonest malignancy in the gastrointestinal tract. It is the third most common cancer of both sexes in the world. It comprised 10.2% of all cancers in 2018. Incidence rates of CRC are increasing in developing countries and survival rates of CRC vary widely. Thus, the aim of the study was to determine two and five year overall survival and its predictors of CRC patients treated at the Oncology Unit, Teaching Hospital, Karapitiya (THK) from 2011 to 2013. A retrospective study was conducted among 151 CRC patients treated at the Oncology Unit, THK from 2011 to 2013. The patients were followed up till 30th September 2020. The patients with secondary CRC were excluded. Clinic records of the Oncology unit were referred to collect data. Patients who had stopped clinic visits were contacted via telephone and letters to identify their current status. Kaplan Meier and Cox’s proportional hazards model were used to model survival. The mean survival times of two year and five-year survival were 21.29 months (SD=5.18) and 44.56 months (SD=20.60) respectively. The median survival times of two year and five-year survival were 24 months and 60 months respectively. The commonest age group was 55 to 64 years (32.5%). The commonest stage of lesions was “Duke’s C” (26.5%). Duke’s stage, nodal status and presence of metastases were statistically significant (P<0.001) independent predictors of survival. Duke’s stage was statistically significant (P<0.001) predictors of survival after controlling for other variables. More than two third of patients (71.5%) survived two years and more than half of the patients (60.3%) survived five years. Duke’s stage was a significant predictor of survival in CRC patients treated at the Oncology Unit, THK.
Keywords: Colorectal cancer; survival; Sri Lanka